Decreased kidney function of unknown cause in Nicaragua: a community-based survey - Torres, Cecilia (2010)
Background: End-stage kidney disease overwhelms health services in Central America. We determined prevalences of decreased kidney function in distinct populations in the most affected region of Nicaragua. Study Design: Cross-sectional survey. Setting & Participants: Total populations aged 20-60 years of 5 villages in Northwest Nicaragua: mining/subsistence farming (elevation, 100-300 m above sea level), banana/sugarcane (100-300 m), fishing (0-100 m), services (0-100 m), and coffee (200-675 m); 479 men and 617 women (83% response). Predictor or Factor: Village; participant sex, age, and occupation; conventional chronic kidney disease risk factors. Outcomes: Serum creatinine (SCr) values greater than laboratory reference range for sex, estimated glomerular filtration rate 60 mL/min/1.73 m2, proteinuria stratified in the low (dipstick protein excretion, 30-300 mg/dL) and high (300 mg/dL) range. Results: Prevalences of abnormal SCr levels: 18% (of all men) and 5% (of all women); in the mining/subsistence farming village, 26% and 7%; banana/sugarcane, 22% and 6%; fishing, 13% and 4%; services, 0% and 1%; and coffee, 7% and 0%. Prevalences of estimated glomerular filtration rate 60 mL/min/1.73 m2: 14% (of all men) and 3% (of all women); in the listed villages, 19% and 5%, 17% and 4%, 10% and 2%, 0% and 0%, and 7% and 0%, respectively. Proteinuria, predominantly in the low range, affected 14% and 11% of all men and women without marked differences between villages. By occupation, abnormal SCr levels occurred in 31% and 24% of male and female agricultural workers at 100-300 m above sea level, but not at higher altitudes, and also was high in male artisans (43%), construction workers (15%), and miners (14%). In logistic regression models, for the banana/sugarcane and mining/subsistence farming villages, high blood pressure and age were significant predictors of abnormal SCr levels in men, and for mining/subsistence farming, age in women. Limitations: Causality is not addressed. Conclusions: In some Nicaraguan villages and population segments, men in particular show a high prevalence of decreased kidney function of unknown origin, possibly environmental or occupational.